Strengthening Marketing Strategies in Organic Agricultural Products Through Organic Farmer Training in Indonesia - Setiawan, Zunan; Dharmawan, Donny; Ariani, Dian; Ekasari, Silvia; Munizu, Musran (Pascasarjana Universitas Mataram, 2024)
This Community Service (PKM) activity aims to improve the marketing skills of organic plant farmers in Indonesia through online training focused on digital marketing strategies, branding development, and distribution network expansion. The method used was participatory training, involving 30 farmers as a sample, with data collection carried out through pre-test and post-tests to measure changes in participants' knowledge and skills. The results showed a significant improvement in participants' understanding of organic product marketing, with the average pre-test score of 2.5 increasing to 4.2 in the post-test. This increase is mainly seen in the ability of participants to utilize social media and e-commerce platforms to market their products. In addition, qualitative interviews showed that participants felt more confident in developing product branding and expanding marketing networks, although challenges related to internet infrastructure were still faced in some areas. Post-training mentoring also provides additional support that helps participants implement the strategies learned. In conclusion, this training is efficacious in improving the marketing skills of organic farmers. It can be a model that can be applied more widely to strengthen the competitiveness of organic agricultural products in Indonesia.